Prediction of Reduction Recovery of Iron and Vanadium Oxides in Low-Grade Vanadium–Titanium Magnetite Based on Response Surface Model - Xueting Jiang; Hao Wu; Aijun Deng (Metals)
In this study, the effects of reduction temperature and time on the reduction rates of iron and vanadium oxides in low-grade vanadium–titanium magnetite (VTM) were investigated. Based on the results of physical experiments, both the response surface method (RSM) and central composite design (CCD) were used to fit the prediction model of the reduction rate of iron and vanadium oxides in low-grade VTM. The results of the RSM prediction model show that under the condition of a sufficient reducing medium, affected by the high-temperature products, such as silicates and magnesium aluminates, the reduction rate of iron and vanadium oxides in low-grade VTM will first increase and then decrease. This indicates that a single factor cannot maximize the reduction efficiency of metal oxides. The results of the RSM prediction model show that the correlation fitting coefficient and correction fitting coefficient of the model are greater than 99% and 98%, respectively. The F-value is 150.05 and 176.19, respectively, and the p-value is less than 0.0001. This indicates that the RSM prediction model has high accuracy and reliability. After parameter optimization of the RSM prediction model, when the reduction temperature is 1446 °C~1498 °C and the reduction time is 43 min~60 min, the maximum reduction rates of iron oxide and vanadium oxide in iron ore can reach 92.93% and 69.20%, respectively. The study of reaction kinetics shows that the reduction processes of iron and vanadium oxides in VTM are controlled by three-dimensional diffusion conditions. The apparent activation energies of the reactions are 86.76 kJ/mol and 90.30 kJ/mol, respectively.